2021
DOI: 10.3390/ijms22052448
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Nociceptin/Orphanin FQ and Dynorphin Systems in the Extended Amygdala of Alcohol Preferring Marchigian Sardinian (msP) Rats

Abstract: Previous studies have shown that genetically selected Marchigian Sardinian alcohol-preferring (msP) rats consume excessive amounts of ethanol to self-medicate from negative moods and to relieve innate hypersensitivity to stress. This phenotype resembling a subset of alcohol use disorder (AUD) patients, appears to be linked to a dysregulation of the equilibrium between stress and antistress mechanisms in the extended amygdala. Here, comparing water and alcohol exposed msP and Wistar rats we evaluate the transcr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…In brief, the amounts of RNA were determined by measuring optical densities and only RNA samples with an OD260/OD280 1.8 < ratio < 2 were used. Total RNA was reverse transcribed as previously described [ 69 , 70 ]. Quantitative real-time PCR was performed on a StepOne Real-Time PCR System (Life Technologies, Carlsbad, CA, USA) using TaqMan Gene Expression Master Mix (ThermoFisher Scientific, Waltham, MA, USA), to analyze SOD1 (Hs 00533490_m1, FAM), β2 (Hs 01002946_m1, FAM), β5 (Hs 00605652_m1, FAM).…”
Section: Methodsmentioning
confidence: 99%
“…In brief, the amounts of RNA were determined by measuring optical densities and only RNA samples with an OD260/OD280 1.8 < ratio < 2 were used. Total RNA was reverse transcribed as previously described [ 69 , 70 ]. Quantitative real-time PCR was performed on a StepOne Real-Time PCR System (Life Technologies, Carlsbad, CA, USA) using TaqMan Gene Expression Master Mix (ThermoFisher Scientific, Waltham, MA, USA), to analyze SOD1 (Hs 00533490_m1, FAM), β2 (Hs 01002946_m1, FAM), β5 (Hs 00605652_m1, FAM).…”
Section: Methodsmentioning
confidence: 99%
“…MsP rats showed increased N/OFQ and NOP receptor expression and ligand-receptor binding in the amygdala and found the site of action of N/OFQ to be the CeA [ 104 ]. Moreover, chronic intermittent ethanol consumption normalized the amygdalar over-expression of PPNOC and NOP genes in msP rats to Wistar level [ 189 ]. Confirming a pivotal role of N/OFQ in mediating the interaction between stress and alcohol in the CeA, N/OFQ was shown to revert CRF-enhanced GABA-mediated inhibitory post-synaptic potentials (IPSPs) in CeA slices of both naïve and ethanol-intoxicated rats [ 101 ].…”
Section: Role Of N/ofq-nop Receptor System In the Interaction Between Stress And Drug Addictionmentioning
confidence: 99%
“…Withdrawal from intermittent cigarette smoke, or e-cigarette vapors, increased depressive and anxiety/obsessive-compulsive-like behaviors, also leading to cognitive impairment. Consonant with the take-home message from the study of Caputi et al [10], an involvement of the CRF-related system was observed, in this case, with an increase in CRF and Crf1 mRNA levels, and a significant downregulation of nociceptin precursor expression upon smoke-withdrawal in the caudate-putamen nucleus (CPu). Smoke withdrawal also decreased brain-derived neurotrophic factor (BDNF) gene expression in the hippocampus, but enhanced its mRNA levels in the CPu.…”
mentioning
confidence: 70%
“…Regarding the first aspect (i), Caputi et al [10] used genetically selected Marchigian Sardinian alcohol-preferring (msP) rats as an experimental model resembling a subset of alcohol use disorder (AUD) patients consuming excessive amounts of ethanol to experience self-relief from negative moods and the innate hypersensitivity to stress. Their results provided evidence for an innate upregulation of the corticotropin-releasing factor (CRF)-related system, together with an inherent upregulation of the opioid-like peptide nociceptin/orphanin FQ (N/OFQ), mediating negative mood and stress responses, at the level of both the amygdala (AMY) and the bed nucleus of the stria terminalis (BNST) of msP rats.…”
mentioning
confidence: 99%